Ensuring the financial security of a motor transport enterprise - Xu, Xu (Харківський національний автомобільно-дорожній університет, 2025)
The paper clarified the concept and essence of financial security of an enterprise, considered the existing criteria and methods for assessing the financial security of enterprises, investigated the mechanism for ensuring financial security on the example of TEK First Capital LLC. Also, the methodological approach to assessing the financial security of the enterprise has been improved and a draft of measures to improve financial security has been proposed, in particular, the introduction of a modern system for monitoring and analysis of fuel consumption.
Keywords: financial security; financial sustainability; financial security management; financial security assessment